Toward a Behavioral Model of "Homegrown" Radicalization Trajectories. (2nd January 2016) - Klausen, Jytte; Campion, Selene; Needle, Nathan; Nguyen, Giang; Libretti, Rosanne
Abstract : This research note presents a dynamic risk assessment model of homegrown terrorists. The model was tested in a study of convicted "homegrown" American terrorism offenders inspired by Al Qaeda's ideology. The New York Police Department model developed by Silber and Bhatt was chosen as the basis for creating a typology of overt and detectable indicators of individual behaviors widely thought to be associated with extremism. Twenty-four specific cues associated with each stage of radicalization were used to code and estimate the sequencing of behaviors and the duration of the average radicalization trajectory. Sixty-eight cases have been analyzed thus far. A decision was made to publish the initial results when it became apparent that the model was an effective tool for the evaluation of terrorist offenders.